KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM KEDARURATAN BENCANA KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN SUMEDANG - Nur Fatwa, Widiyanti (LPPM UNSAP & FISIP UNSAP, 2024)
This study aims to identify, process data, analyze, and measure the performance of regional disaster management agencies (BPBD) in forest and land fire disaster emergencies in Sumedang Regency. The method used in this study is a qualitative method with a descriptive type. The research informants consisted of: Chief Executive, Secretary, Head of the Emergency and Logistics Section, and Operation Logistics Data Center. The data collection technique is literature study, and field study consisting of observation, interview, and documentation. Meanwhile, data processing techniques are data reduction, data display, data conclution drawing/verification and triangulation. Based on the results of the study, it was concluded that to measure organizational performance in terms of productivity, service quality, responsiveness, responsability and accountability are good. The inhibiting factors lie in individual abilities and the work environment, namely the lack of human resources who are geologists, hydrometologists and other experts, lack of employee concentration and lack of supporting facilities and infrastructure so that efforts are made to improve the work ability of employees through training, adding supporting infrastructure. Suggestions in this study include being more active in conducting socialization, counseling, and simulation to the community, completing the necessary facilities and infrastructure, improving the quality of resources in accordance with the competence of experts in the field of geology, hydrometheologists and other experts.